Motivasi Switching Intention Nasabah Bank Syariah Indonesia (BSI) Wilayah Maluku Utara Pasca Merger di Era Pandemi Covid-19 - Hajar, Hasbullah (Research Center and Case Clearing House PPM School of Management, 2025)
Technological disruption due to Covid-19 is a challenge for banking sector businesses to maintain the business sustainabiilty, considering that offline service which were initially the focus of best practice, then had to be changed to online services. In an effort to maintain business sustainability, several state-owned sharia banking companies merged to become Bank Syariah Indonesia (BSI), and this is interesting because the merger was carried out at the beginning of Covid-19 in Indonesia. This research aims to identify the influence from E-Channel service variable on the switching intention of BSI customers in North Maluku, moderated by the Covid-19. The population is BSI North Maluku customers. The sampling method used was purposive sampling and a total of 212 respondents were found. This research uses the SEM-PLS analysis method with the consideration that this research tends to be exploratory research. The results of this research show that ease of E-Channel service can reduce the switching intention of BSI customers in North Maluku. Meanwhile, providing easy E-Channel services during Covid-19 force majeure conditions was able to help reduce BSI customers' switching intention but was deemed not statistically significant enough, resulting in the second hypothesis being rejected. The findings in the research show that BSI does not have to consider certain factors to improve its E-Channel service, considering that customer loyalty is fundamentally influenced by the optimality of the E-Channel service itself.